The Impact of Carbonization Temperature on The Quality of Empty Fruit Bunch Charcoal and Palm Kernel Charcoal for Co-Firing Application - Febriani, Annisa Vada; Hanum, Farrah Fadhillah; Rahayu, Aster; Setya Wardhana, Budi; Firda Mahira Alfiata Chusna (Sains Natural: Journal of Biology and Chemistry, 2025)
Biomass is a renewable energy source that can be processed into charcoal through a carbonisation process, which depends on temperature to improve the quality of the charcoal produced.  This research focuses on the utilisation of Oil Palm Fronds (OPF) and Palm Kernel Shells (PKS) as biomass feedstock in an effort to produce an alternative fuel that can be used in the co-firing process with Low Rank Coal (LRC). This study heats palm fronds and shells at 300°C to 600°C, then measures moisture content, ash content, calorific value, and sulfur content. Based on the results, a temperature of 600°C was identified as the optimal condition for the OPF and PKS drying process. At this temperature, a significant decrease in moisture content is directly proportional to the increase in ash content and calorific value, indicating an improvement in fuel quality. The highest calorific values achieved were 6095.35 kcal/kg for OPF and 7364.81 kcal/kg for PKS. In addition, the sulphur content of the charred biomass is much lower than that of coal, which provides an advantage in terms of cleaner emissions. In comparison with LRC, the charred biomass showed better quality in terms of calorific value and lower sulphur content, despite the higher ash content of the biomass. OPF and PKS that have undergone the charring process offer a more environmentally friendly fuel alternative and have the potential to replace LRC in combustion applications, resulting in lower emissions. This study thus reinforces the potential of oil palm biomass as a promising renewable energy source.